Realization of Universal Quantum Gates with Spin‐Qudits in Colloidal Quantum Dots. Issue 10 (1st July 2019) - Moro, Fabrizio; Fielding, Alistair J.; Turyanska, Lyudmila; Patanè, Amalia
Abstract: Hyperfine interactions in a single Mn‐ion confined in a quantum dot (QD) are exploited to create a qudit, that is, a multilevel quantum‐bit system, with well‐defined, addressable, and robust set of spin states for the realization of universal quantum gates. An arbitrary superposition of states between selected hyperfine energy level pairs is generated and probed by using electron double resonance detected nuclear magnetic resonance (EDNMR). This enables the observation of Rabi oscillations and the experimental realization of NOT and SWAP universal quantum gates that are robust against decoherence. Our protocol for cyclical preparation, manipulation, and read‐out of logic gates offers opportunities for the integration of qudits in scalable quantum circuit architectures beyond solid state electron spin qubits . Abstract : Hyperfine interactions in a single Mn ion confined in a quantum dot create a qudit, that is, a multilevel quantum‐bit system with well defined, addressable, and robust set of spin states. Electron double resonance detected nuclear magnetic resonance (EDNMR) enables the implementation of universal quantum gates beyond traditional 2‐level spin qubits with potential for low‐cost, scalable, and downsized quantum computer architectures.